Geometric Redesign of Jalan Cisauk–Jaha, Banten with Manual Method (Sta. 0+000-Sta. 0+350) - Rizki, Rizki; Rifai, Andri Irfan; Djamal, Endry Z. (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Expected to guarantee user comfort and safety, enable efficient traffic operations, and simultaneously attract the minimum possible costs in construction and maintenance. The construction of the Jalan Cisauk-Jaha in Banten Province is one of the projects of the Public Works and Planning Office of Banten Province. This paper aims to redesign a safe horizontal alignment for motorists to pass on the Jalan Cisauk–Jaha using the Bina Marga method at STA 0+000 – 0+350 where there is one bend or horizontal alignment. The method used in planning is the Bina Marga method. The research results of the horizontal alignment and geometric planning for the Cisauk–Jaha Highway STA 0+000 – 0+350 time attract the minimum possible costs in construction and maintenance. The construction of the Jalan Cisauk-Jaha in Banten Province is one of the projects of the Public Works and Planning Office of Banten Province. This paper aims to plan a safe horizontal alignment for motorists to pass on the Jalan Cisauk-Jaha using the Bina Marga method at STA 0+000 - 0+350 where there is one bend or horizontal alignment. The method used in planning is the Bina Marga method. The results can be concluded that the Cisauk–Jaha Highway is a class IIA collector road with a width of 7 meters and design speed (VR) of 80 km/hour, design parameters, and a maximum slope (e) of 8%. From the calculation, the design radius (R) is 210 m, with the intersection angle (°) of 48°, the horizontal curved length (Lc) of 196.43 m, the maximum slope (e) of 8%, and the road terrain class being a flat area.